Diseño de un sistema didáctico para el aprendizaje del control de procesos, estudio de caso control de flujo para el laboratorio de investigación de automatización y control de la carrera de Ingeniería Electromecánica de la Universidad Técnica de Cotopaxi. - Caillagua Cuyo, Erick Javier (2021)
In this degree project, a didactic flow control system was designed through a virtual reality environment for learning process control in the Automation and Control Research Laboratory of the Technical University of Cotopaxi. And with respect to the simulation of the virtual process, the mathematical model of the real plant was obtained to obtain the behavior of the process in real time and through the MATLAB software the transfer function was acquired, which was used to increase the realism of the virtual didactic system. . The virtual environment was designed in the Unity3D software which reflects the existing real plant of the laboratory, it emulates the operation of the system in real time, in addition an HMI was developed for the control and monitoring of the flow variables, where the data was acquired. from the programmable logic controller (PLC S7-1200) through a NI_OPC_Server interface, a programmed block for a TCP/IP communication with Unity3D was also created. In this way, the practices of measurement and comparison of flow variables were carried out through a virtual environment in order to be able to evaluate them through the theory of measurement errors in the technical area of Instrumentation and Control of the Electromechanical Engineering Career.